SIGNIFICANCE AND USE OF MEDICAL TERMINOLOGY IN RUSSIAN LESSONS FOR UZBEK STUDENTS OF MEDICAL UNIVERSITIES - Irbutaeva Nigora Dilshodovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article focuses on the use of medical terms and abbreviations, the selection of synonyms that cause difficulties in understanding, interpreting and pronouncing them by non-russian-speaking students.